2020
DOI: 10.1002/mds.28023
|View full text |Cite
|
Sign up to set email alerts
|

A Homozygous Splicing Mutation in PDE2A in a Family With Atypical Rett Syndrome

Abstract: 250-mg challenge dose produced a 41% improvement in UPDRS-III with dyskinesia (Supporting Information Table S1). However, she developed FOG on gait initiation, straight walking, doorways, and turning. FOG was associated with rising up onto the toes during straight walking and onto the toe of the outer rotating foot when turning, raising the possibility of a dystonic phenomenon (Video 2). She was diagnosed with on-state FOG. L-dopa was changed to immediate release and fractionated, amantadine 200 mg daily added… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 8 publications
3
13
1
Order By: Relevance
“…Consistently, Doummar et al, 2020 3 reported paroxysmal dyskinesia in patient 3 starting at 7 years, occurring 30–50 times per day with each attack lasting between 2–5 min. Of the 12 patients with biallelic PDE2A variants, only four display permanent choreodystonia (2/6 in this study and 2/6 in the previous patients), 3,7,8 reflecting that this is an inconsistent outcome of the disease. In line with the published data, 3,7,8 ID has been witnessed in all patients.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…Consistently, Doummar et al, 2020 3 reported paroxysmal dyskinesia in patient 3 starting at 7 years, occurring 30–50 times per day with each attack lasting between 2–5 min. Of the 12 patients with biallelic PDE2A variants, only four display permanent choreodystonia (2/6 in this study and 2/6 in the previous patients), 3,7,8 reflecting that this is an inconsistent outcome of the disease. In line with the published data, 3,7,8 ID has been witnessed in all patients.…”
Section: Discussionmentioning
confidence: 56%
“…Biallelic variants in PDE2A are known to cause IDDPADS, an ultra‐rare disease for which only six patients have been reported so far 3,7,8 . WES revealed a novel homozygous missense variant in PDE2A : p.(Phe505Ser) as a potential causative variant that segregated with the disease in three Pakistani families presenting paroxysmal dyskinesia, developmental delay, cognitive abnormalities, speech impairment and seizures with onset as early as 3 months in Family C to 7 years in Family A.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The modulation of cAMP and cGMP has been also reported to be key in learning and memory. Indeed, mutations of PDE2A have been found associated with intellectual disability [ 22 , 51 , 52 ] and PDE2A seems to have a prominent role in memory disorders [ 53 55 ]. Several studies have shown that Fmr1 -KO mice display cognitive impairments [ 56 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…PDE2A is a dual-specific PDE that breaks down both cAMP and cGMP and is activated by cGMP. A homozygous splicing mutation in PDE2A was found in two patients with atypical Rett syndrome (RTT), displaying neurodevelopmental delay [ 34 ], while a homozygous loss-of-function mutation in PDE2A was associated with early-onset hereditary chorea-predominant movement disorder and intellectual disability (ID) [ 35 ]. Patients with bipolar disorder showed reduced PDE2A mRNA levels in the hippocampus, caudal entorhinal cortex, and striatum, while patients with SCZ, bipolar disorder, and major depressive disorder (MDD) showed reduced PDE2A mRNA levels in the amygdala.…”
Section: Introductionmentioning
confidence: 99%